SUPERVISI KEPALA SEKOLAH MEMODERASI PENGARUH DISIPLIN KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU (Studi Di SMP Negeri Sub Rayon 05 Kota Semarang) - 11.52.02.0150, Safroni (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to examine the effect of work discipline, teacher competence, principal supervision on teacher performance (Study in junior high school teachers in sub rayon 05 kota Semarang). Specific objectives of this study to examine whether the moderating influence of the principal supervision of work discipline, and teachers competence on teacher performance.This study used a sample of junior high school teachers in sub rayon 05 kota Semarang as many as 175 teachers. This study uses a single period in 2013. Sampling technique in this study was a census technique, meaning that all of the population is made the object with the method of data collection using primary data is data obtained from respondents answers to the questions posed in the questionnaire related to teacher discipline, teacher competence, principal supervision and teacher performance comes complete with the identity of the respondents. About 175 questionnaires distributed 161 were returned, and then analyzed using SPSS19.The results showed that: (1) Work Discipline and teacher competence have a significant and positive effect on teacher performance, (2) Principal Supervision did not moderate the influence of work discipline on teacher performance instead principal supervision moderated influence of teacher competence on teacher performance. Keyword : Work Discipline, teacher competence, principal supervision and teacher performance.